Furuncular myiasis caused Dermatobia hominis in a Slovenian traveler - Bartenjev, Mark Sergej (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2025)
A case of furuncular myiasis caused by the larva of Dermatobia hominis is described, involving the ankle region of a 35-year-old woman that had returned from a vacation in Colombia. After removal of the larva from the skin, the lesion healed in 2 weeks. Due to an increasing rate of intercontinental travel, dermatologists in Slovenia may need to consider Dermatobia myiasis in the differential diagnosis of furuncular lesions in patients with a relevant travel history.
Keywords: botfly; Dermatobia hominis; furuncular myiasis; furunkularna miaza; muha bot; muha gnojarica; parasitic skin infections; parazitska muha; parazitske okužbe kože; tropical diseases; tropske bolezni